Enhancing Patient Choice Through the Development of Physical Therapist Online Biographies - Evan K Perrault PhD; Jeff Stein PT, ATC, DPT (Journal of Patient Experience)
Provider web profiles are becoming popular locations for patients to seek information before their visits. This industry insight assesses patients’ utilization of a physical therapy clinic's website to determine the impact the addition of physical therapist biographies had on patient perceptions and physical therapist selection. Forty-six percent of first-time patients ( n  = 786) indicated visiting the clinic's website prior to their visit. After biographies were added, these website visitors rated the website as more helpful, and indicated a greater perception of certainty regarding the services the clinic provides. A greater percentage of website visitors made a purposeful selection of therapist after therapist biographies were posted online than prior to biographies being posted. These findings indicate that improvements to a clinic's website can positively impact patient empowerment in making personal healthcare decisions. Simply adding biographies of physical therapists to clinics’ websites can have significant effects on reducing first-time patients’ uncertainty, as well as providing a greater level of patient-centered care by offering information to empower patients to be more active participants in their healthcare choices.